America, India, and Kashmir, 1945–49: "If Ignorance About India in This Country is Deep, Ignorance About the [Princely] States is Abysmal"1. Issue 1 (2nd January 2016) - Ankit, Rakesh
ABSTRACT: This analysis offers an alternative examination of American interest in India in the mid-1940s and situates the early American attitude to Kashmir into that matrix. The two years from 1945 to 1947, those of the emergence of decolonisation and the Cold War, critically influenced America's attitude first towards India and then towards Kashmir. It has been commonplace to describe America's early understanding of the Kashmir conflict as an issue unconnected with the Cold War until 1952–1954. Even those works, which argue for an early presence of an "east-west lens" in the American consciousness, begin from either the Communist triumph in China or the outbreak of the Korean War. This analysis, instead, shows how soon, how much, and how comprehensively various sections of American government looked at Kashmir through an international prism.